2010
DOI: 10.1038/ismej.2010.103
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics reveals a deep-sea sediment-adapted life style of Pseudoalteromonas sp. SM9913

Abstract: Deep-sea sediment is one of the most important microbial-driven ecosystems, yet it is not well characterized. Genome sequence analyses of deep-sea sedimentary bacteria would shed light on the understanding of this ecosystem. In this study, the complete genome of deep-sea sedimentary bacterium Pseudoalteromonas sp. SM9913 (SM9913) is described and compared with that of the closely related Antarctic surface sea-water ecotype Pseudoalteromonas haloplanktis TAC125 (TAC125). SM9913 has fewer dioxygenase genes than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
89
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(91 citation statements)
references
References 63 publications
2
89
0
Order By: Relevance
“…Third, virus-directed augmentation of motility is suggested by ACE POV-encoded pseudaminic synthase (pseI), which likely glycosylates flagellins (Hopf et al, 2011). Flagellar genes (flaB and motA) are critical for maintaining mobility and particle association for deep sea bacteria (Eloe et al, 2008;Qin et al, 2011). Such genes for 'chemotaxis and motility' have been observed previously in viromes (Dinsdale et al, 2008) and may boost their host's motility to improve nutrient acquisition in the deep sea.…”
Section: Co-localized With Viral Genes On Contigs (Includes Genes Idementioning
confidence: 99%
“…Third, virus-directed augmentation of motility is suggested by ACE POV-encoded pseudaminic synthase (pseI), which likely glycosylates flagellins (Hopf et al, 2011). Flagellar genes (flaB and motA) are critical for maintaining mobility and particle association for deep sea bacteria (Eloe et al, 2008;Qin et al, 2011). Such genes for 'chemotaxis and motility' have been observed previously in viromes (Dinsdale et al, 2008) and may boost their host's motility to improve nutrient acquisition in the deep sea.…”
Section: Co-localized With Viral Genes On Contigs (Includes Genes Idementioning
confidence: 99%
“…The genus contains specialists for various marine habitats ranging from sea ice (9) to deep-sea sediments (10). Its species are divided into pigmented and nonpigmented species; the former are known for habitation of marine biofilms and production of antimicrobial and algicidal substances, while the latter are found living dispersed in the water column (11).…”
mentioning
confidence: 99%
“…SM9913 (GenBank accession no. ADT69962) (26). b All reactions were carried out at both 30°C and 60°C, and activities with the highest values are shown.…”
Section: Discussionmentioning
confidence: 99%
“…SM9913 (PsEst) (GenBank accession no. ADT69962) (26), which showed 56% to 66% identity with respect to Est22, were chosen for a study of their substrate specificities. The results showed that all three Est22 homologs could efficiently hydrolyze short-chain pNP esters (C 2 to C 6 ) and had no detectable transacetylase activity (Table 3), just as in the case of Est22.…”
Section: Discussionmentioning
confidence: 99%